Strategy for Optimizing Coastal Village Communities in Supporting the Protection of Essential Ecosystem Areas in Gresik Regency - R. Achmad Djazuli; Garist Sekar Tanjung; Kurniawan Ramadhani; Mochammad Afif Lutf (Agricultural Science, 2021)
This study aims to (1) identify the behavior of local communities in the use of mangrove forests, (2) analyze the factors that influence the utilization of mangrove forests, and (3) develop strategies for optimizing the use of mangrove forests in the context of empowering coastal communities and preserving the environment. The research location was determined purposively, namely in Ujung Pangkah District, Gresik Regency as one of the areas designated as Essential Ecosystem Areas (KEE). The analytical method used is descriptive analysis. The results showed that (1) the characteristics of the damage to mangrove forests in the area were changes in the function of the area due to the conversion of community functions into cultivation areas, (2) the factors that influenced the success of mangrove conservation as KEE, namely: (a) socio-economic conditions and the culture of the community is the same, namely the level of education and income of the community is relatively low, (b) the function of community institutions is not optimal (c) local wisdom and local resilience, (d) community perceptions of the mangrove ecosystem are less positive on sustainability, (3) strategies that can be implemented among others (a) Increasing the quantity and quality of human resources (b) socio-economic development of the community, (3) optimizing the functions of formal and non-formal institutions of society, and (4) procuring laws and regulations